Effects of COVID-19 on environmental conditions and poultry production - Areeb Ahmer; Muhammad Hamza; Ayesha Muazzam; Abdul Samad; Sania Tariq; Shehroz Ahmad; M.Talha Mumtaz (Brilliance: Research of Artificial Intelligence, 2022)
Although hens are not vulnerable to SARS-CoV-2, there have been a number of coronavirus illness outbreaks reported in connection with poultry processing plants in various nations. The COVID-19 pandemic and the created strain triggered the second, third, and most current waves of epidemics, which had unforeseen effects such being obliged to reduce demand for certain sectors, transit systems, jobs, and enterprises owing to public confinement. Additionally, because of the close closeness on the line, the cold, and the humidity, the circumstances in chicken processing factories increase the dangers. Due to poor pay and lack of access to paid sick days or proper healthcare, the majority of employees have little money saved up in case they choose to quit their stable jobs. Additionally, employees at meat and poultry slaughterhouses may get an infection via touching filthy workstations, dining room tables, or equipment, as well as from respiratory droplets in the air. Due to consumer behaviour changes brought on by the lockout, egg costs have climbed significantly. Over the next months, the COVID epidemic may have a significant influence on the world poultry trade as well. The impact of COVID-19 on chicken production, environmental sustainability, and earth systems will be the main emphasis of this study from many process angles.